Research on Implementation Methods of Wired Access Service Resource Allocation Rules and Technologies - Jie Yin; Jingjing Bao; Wenjun Shen; Zhiting Peng (Dianxin kexue)
Access service configuration is almost most complicated procedure in service provision process. In past few years, many cases of access service configuration were analyzed, and some factors were found to make rules. These rules could guide the action of configuration to meet the complex needs of customers. The rule engine was used to run these rules in resource management system.